2016
DOI: 10.1039/c5tc03750f
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromic properties of vertically aligned Ni-doped WO3 nanostructure films and their application in complementary electrochromic devices

Abstract: High-contrast electrochromic device of tunable color change from transparent to black were achieved with vertically aligned Ni-doped WO3 films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(40 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…Fermi energy level ( E f ) is located at the range of conduction band, in agreement with the former reports that PWO belongs to conductor. [20b] In the primitive crystal model of W 18 O 49 , the sites of W atom are labeled in letters from “A” to “R” and Ni‐doped tungsten oxide with specified substitution are labeled as NWO‐X (X: “A” to “R,” Figures S1 and S4, Supporting Information). In the figure of density of state (DOS) (Figure b) of NWO‐L (Figures S5–S7, Supporting Information), the DOS at E f increases (Figure b and Table S1, Supporting Information) owing to the contribution of the d orbit for Ni (Figure S7, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fermi energy level ( E f ) is located at the range of conduction band, in agreement with the former reports that PWO belongs to conductor. [20b] In the primitive crystal model of W 18 O 49 , the sites of W atom are labeled in letters from “A” to “R” and Ni‐doped tungsten oxide with specified substitution are labeled as NWO‐X (X: “A” to “R,” Figures S1 and S4, Supporting Information). In the figure of density of state (DOS) (Figure b) of NWO‐L (Figures S5–S7, Supporting Information), the DOS at E f increases (Figure b and Table S1, Supporting Information) owing to the contribution of the d orbit for Ni (Figure S7, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, heteroatom doping has emerged as an effective strategy to generate active sites[17c,18c] and regulate electronic structure to modify the performance of tungsten oxide. [17b,20] For example, the introduction of Mo element can efficiently optimize the electronic structure and thus significantly improve the hydrogen evolution reaction (HER) performance. [17c] Further, nonmetal elements such as elemental C can play the similar role in the optimization of electron structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Said differently, the electrical and optical properties that vary by carrier concentration and mobility of the WO 3 layers mainly determine the kinetics of the EC reactions. Therefore, many studies on the doped nanostructures have used suitable metal ions with a lower oxidizing capability or a higher electronegativity compared to those of host ions, such as Ti, Ni, Fe, and P. [19][20][21][22] Interestingly, in addition to the modification of electrical and optical properties on the host EC materials, this approach can induce a variation of morphology or crystallinity, which is expected to benefit the EC performances of switching speed, CE, and cycling retention. As a major result, Cai et al reported the hierarchical structure Ti-doped WO 3 films prepared using the hydrothermal method (see Figure 3a).…”
Section: Doped Nanostructuresmentioning
confidence: 99%
“…Doping with metal ions (such as Ni and Ti, among others) has been widely investigated as another strategy for making high-performance WO 3 electrochromic materials. [24][25][26][27] Bathe et al investigated the inuence of Ti doping on the electrochromic properties of WO 3 thin lms prepared by pulsed spray pyrolysis, and suggested that doping WO 3 with Ti induced a phase transformation from monoclinic to amorphous and a rough surface morphology, resulting in improvement in the cycle stability, charge storage capacity, and reversibility of the lms. 24 Cai et al prepared Ti-doped WO 3 lms with a hierarchical star-like structure by a hydrothermal method, where the star-like structure had a low charge-transfer resistance and ion diffusion resistance, leading to fast switching speed and high coloration efficiency.…”
Section: Introductionmentioning
confidence: 99%